(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The article highlights the lexical-semantic, phraseological, historical-etymological, and lexicographical features of such units as halva, pashmak, parvarda, and baklava, which are part of the confectionery concept